Pemanfaatan Sumber Belajar IPS dalam Proses Pembelajaran Daring di MTs Sultan Agung Srati - Octaviani, Nurul Army; Mulianingsih, Ferani (Universitas Negeri Semarang, 2021)
Region potential-based learning is reflected goverment regulations in the 2013 curriculum, where students must be able to link knowledge with all aspects of life. This study used qualitative research methods. Data collections tecniques throught observation interviews, and documentation. Data sources were obtained from primary and secondary data sources. The validity test in the study used triangulation and data analysis techniques consisted of data collection, data reduction, data presentation and drawing conclusions. The results showed that the learning implementation plan as a result of the covid-19 pandemic. In implementating the learning proces the teacher use the social studies package book and the Menganti Beach tourism booklet as a social science learning resources. The focus of the material in this research is natural resources and maritime materials. The output of the learning is the from of a summary of the material potential of natural and maritime resources. The obstacles found were the lack of learning resources, limited learning media and internet networks.